Discussing the potentialities of video tutorials to distance learning - Forno, Josiane Dal (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
It is observed that teachers, in general, use of a limited available resources in the virtual learning environment (VLE) and others external to it which could be inserted in this expanding training opportunities offered both classroom teaching, as distance education. Thus, this paper aims to present the process of construction of tutorial videos and discuss its use in educational activities in different educational modalities. For this study, we used, at first, a literature about the main issues involved in the production and use of video tutorials. To understand and promote the use tutorial videos as educational resources for teachers of university teaching, distance education and classroom teaching, broke for creating some videos. The process of creating a video tutorial involves different steps and specific knowledge, especially concerning the characteristics and potentials of different softwares.